Prevalence and Determinants of Malnutrition among Under-Five Children in a Rural Village in Giza Governorate - Hagag, Suzan; Nasser, Shafika; Elden, Nesreen Mohamed Kamal; Taha, Asmaa Mohamed (Open Access Macedonian Journal of Medical Sciences, 2022)
BACKGROUND: Malnutrition remains a serious problem to child survival, growth, and development in underdeveloped countries. AIM: The aim of this study is to assess the prevalence and determinants of malnutrition among under-five children. METHODS: This study is a cross-sectional community-based study. It was conducted on 320 mother-child pairs through household visits in Nahia; a rural village in Giza governorate, Egypt. A structured questionnaire was developed to collect data regarding sociodemographic characteristic, feeding pattern, including breastfeeding and weaning practices. Anthropometric measurements (weight, height) and Hb level were measured for all the studied participants. RESULTS: The mean age of the children was 35.98 ± 15.8 months, and the mean age of mothers was 28 ± 4.6 years. Stunting was found in 16.2%, wasting in 9%, and underweight in 15.6% of children, with a total malnutrition of 79 (24.7%). Nearly half of children were anemic(51.2%). Many risk factors were contributing to malnutrition as socioeconomic status, age of mother at giving her first birth, and child birth weight. CONCLUSION: Stunting and anemia were the predominant nutritional problems among children so nutritional counseling for mothers is needed to improve feeding practices of their children.